2016
DOI: 10.1140/epjc/s10052-016-3904-4
|View full text |Cite
|
Sign up to set email alerts
|

Noninertial effects on the quantum dynamics of scalar bosons

Abstract: The noninertial effect of rotating frames on the quantum dynamics of scalar bosons embedded in the background of a cosmic string is considered. In this work, scalar bosons are described by the Duffin-Kemmer-Petiau (DKP) formalism. Considering the DKP oscillator in this background the combined effects of a rotating frames and cosmic string on the equation of motion, energy spectrum and DKP spinor are analyzed and discussed in details. Additionally, the effect of rotating frames on the scalar bosons localization… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
81
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 82 publications
4
81
0
1
Order By: Relevance
“…We can note that the allowed energy values forn = 1 are influenced by the spacetime with LSV through the presence of the constant parameters a and g. Note that, by making ν = 0 in the Eqs. (77) and (78) we recover the Eqs. (50) and (51), respectively.…”
Section: Z-directionmentioning
confidence: 93%
“…We can note that the allowed energy values forn = 1 are influenced by the spacetime with LSV through the presence of the constant parameters a and g. Note that, by making ν = 0 in the Eqs. (77) and (78) we recover the Eqs. (50) and (51), respectively.…”
Section: Z-directionmentioning
confidence: 93%
“…Moreover, to make a consistent quantum field theory in a gravitational background, it is necessary to analyze the single particle states, in this way, efforts have been made in order to find an adequate formulation of the relativistic equation of motion for particles in a curved spacetime. In recent years, there has been a significant increase of interest in the study of gravitational effects on quantum mechanical systems (single particle states) [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. In this context it has been shown that the energy spectrum associated with one-electron atoms in an arbitrary curved spacetime is different from the one obtained in the usual flat Minkowski spacetime [4].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the KG equation with interactions (the most general Lorentz structure) consists in vectors (A µ and X µ ), and scalar (V s ) potentials. Scalar particles in the background space-time generated by a cosmic string are very interesting systems that have been studied extensively in the literature in recent years [15][16][17][18][19][20]. A natural question arises, whether the presence of such kind of topological defect can also influence the behavior of scattering states and bound states of a given quantum system.…”
Section: Introductionmentioning
confidence: 99%